Three new species of the genus Lasianobia Hampson, 1905 (Lepidoptera, Noctuidae) from China, with a revised checklist for the genus - Saldaitis, Aidas; Volynkin, Anton V.; Truuverk, Andro (Zootaxa, 2018)
Three new species of Lasianobia Hampson, 1905 are described from China: Lasianobia dvoraki Saldaitis, Volynkin & Truuverk, sp. nov. (W Sichuan), Lasianobia labranga Saldaitis, Volynkin & Truuverk, sp. nov. (SW Gansu) and Lasianobia qinghana Saldaitis, Volynkin & Truuverk, sp. nov. (Qinghai). Adults and male genitalia of these new species and their relatives are illustrated, and a generic check list presented.